The Influence of Long Time and Quality of Mother's According Through Peer Group Support on Behavior Changes and Debris Index in Children with Disabilities - Endah Aryati Ekoningtyas; Irmanita Wiradona; Prasko Prasko; Benni Benyamin (Jurnal Kesehatan Gigi, 2022)
Children with special needs have limited intelligence and motor skills that cause a lack of dental and oral health maintenance. Children with special needs are at risk of developing dental and oral diseases. Therefore, it is very necessary to assist parents in maintaining the dental and oral health of children with special needs. Assistance for parents of children with special needs has been carried out 4 times in a period of 2 years on an ongoing basis. The purpose of this study was to determine the effect of the length and quality of maternal assistance on behavioral changes and the debris index of children with special needs in Meteseh. This type of research is pre-experimental with a pretest and posttest one group design. The sample in this study were 30 parents and children with special needs. Data analysis used univariate and bivariate analysis, Wilcoxon test to determine differences in knowledge and attitudes of crew members and debris index before and after treatment. The Mann-Whitney Test was used to determine differences in the knowledge and attitudes of parents of children with disabilities to changes in debris index of children with disabilities. The results obtained indicate an increase in the knowledge and attitudes of children with disabilities Sparents. The debris index of children with disabilities Shas decreased but is still not enough to change the children with disabilities 's actions in maintaining dental and oral health into a good category. Assistance to parents of children with special needs needs to be carried out further and children with special needs still need more parental participation to achieve good dental and oral health measures.